The Implementation of Bilingual Education in Teaching and Learning at SMP Aqobah International School: (A Case Study of Bilingual Education Using English-Indonesian in Mathematics Lessons for Class VIII) - Jannah, Roudhotul; Fajarina, Maskhurin (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This study investigates the implementation of bilingual education using English and Indonesian in mathematics instruction at SMP Aqobah International School. The research aims to explore how bilingual education is applied and to identify the challenges faced during its implementation. Employing a descriptive qualitative method, data were collected through observations, interviews with students, teachers, and school administrators, as well as questionnaires distributed to eighth-grade students. The findings reveal that the school adopts a bilingual teaching approach aligned with the Cambridge curriculum, where English is used predominantly, while Indonesian serves as a supportive language to aid comprehension. Teachers function as facilitators and motivators, employing various strategies such as interactive lectures, group discussions, vocabulary lists, and technology-based tools. Despite its benefits in enhancing students' English skills and mathematical understanding, the program encounters challenges including students’ difficulty in understanding English terms and lack of speaking confidence. Overall, bilingual education at SMP Aqobah International School fosters a supportive and globally oriented learning environment. The study highlights the importance of teacher training and appropriate instructional materials to optimize the bilingual learning process.